2019
DOI: 10.1101/847756
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neural correlates of evidence and urgency during human perceptual decision-making in dynamically changing conditions

Abstract: Current models of decision-making assume that the brain gradually accumulates evidence and drifts towards a threshold which, once crossed, results in a choice selection. These models have been especially successful in primate research, however transposing them to human fMRI paradigms has proved challenging. Here, we exploit the face-selective visual system and test whether decoded emotional facial features from multivariate fMRI signals during a dynamic perceptual decision-making task are related to the parame… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 63 publications
4
23
0
Order By: Relevance
“…As with our previous work (Yau et al, 2020), we observed two distinct groups of individuals based on performance under the ambiguous condition ( Fig. 3) : (1) early responders (n=32), who on >=80% of ambiguous trials responded during the first two-thirds of the trial before information ramped towards one direction and (2) the rest, who were categorized as late responders (n=25).…”
Section: Tendency To Wait: Early Versus Late Responderssupporting
confidence: 82%
See 4 more Smart Citations
“…As with our previous work (Yau et al, 2020), we observed two distinct groups of individuals based on performance under the ambiguous condition ( Fig. 3) : (1) early responders (n=32), who on >=80% of ambiguous trials responded during the first two-thirds of the trial before information ramped towards one direction and (2) the rest, who were categorized as late responders (n=25).…”
Section: Tendency To Wait: Early Versus Late Responderssupporting
confidence: 82%
“…At any given time t, the evidence E (i.e., level of information/facial emotion level) is multiplied by an attentional fixed gain term g. An intra-trial Gaussian noise variable G(0,N) with a mean of 0 and a standard deviation of N was added. A N of 6 was chosen based on previous work (Carland et al, 2015;Yau et al, 2020) and because it gave a range of simulated RTs with similar variability as the observed data in our current study. The time constant determines how far back in time sensory information is considered by the model.…”
Section: Urgency Gating Modelmentioning
confidence: 96%
See 3 more Smart Citations